Comparing the severity of chronic rhinosinusitis symptoms before versus during the COVID‐19 pandemic - Jasmine S. Lin; Bruce Tan; Chen Yeh; Robert Kern; David Conley; Kevin Welch; Anju Peters; Stephanie Smith (Laryngoscope Investigative Otolaryngology, 2022)
Abstract Background COVID‐19 measures such as masking, social distancing, and staying indoors may mitigate chronic rhinosinusitis (CRS) symptoms. We evaluate whether these measures correlated with improved symptoms in patients with CRS. Methods This retrospective study compared SNOT‐22 survey data from the Northwestern CRS Registry at the time of enrollment and at years 1–5 of follow‐up. The final sample consisted of 1826 SNOT‐22 surveys for 598 patients. April 10, 2020 to December 31, 2021 was considered "during the pandemic" and prior to March 11, 2020 was considered "pre‐pandemic." Wilcoxon test was used to compare SNOT22 at enrollment pre‐pandemic versus during pandemic. Separate linear mixed models were performed to estimate SNOT22 at 1 to 5 years after enrollment pre‐pandemic versus during pandemic. Results Subjects enrolled during the pandemic had worse SNOT22 scores than those enrolled pre‐pandemic (53 vs. 42, p = .0024). Total SNOT‐22 scores were improved during the pandemic than before the pandemic at 1 year follow‐up (18.17 vs. 12.22, p = .001). This effect persists when evaluating the nasal (7.33 vs. 5.13, p = .003), sleep (2.63 vs. 1.39, p = .008), function (1.40 vs. 0.72, p = .015), and emotion (0.77 vs. 0.17, p < .001) domains individually. There was no statistically significant difference in total SNOT‐22 score at Years 2–5 of follow‐up. Conclusions Patients with CRS experience a greater reduction in symptom severity in their first year of treatment during the pandemic than before the pandemic, plausibly from measures such as masking and staying indoors. Level of Evidence 4